2006
DOI: 10.1063/1.2351675
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of hydrated sulfate dianions

Abstract: We report the first infrared spectra of multiply-charged anions in the gas phase. The spectra of SO(4) (2-)(H(2)O)(n), with n=3-24, show four main bands assigned to two vibrations of the dianionic core, the water bending mode, and solvent libration. The triply degenerate SO(4) (2-) antisymmetric stretch vibration probes the local solvent symmetry, while the solvent librational band is sensitive to the hydrogen bonding network. The spectra and accompanying electronic structure calculations indicate a highly sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
180
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 115 publications
(208 citation statements)
references
References 26 publications
25
180
1
2
Order By: Relevance
“…This led to a greater number of dangling water O-H bonds compared to the sulfate-water case, where the suppression of dangling O-H bonds (compared to pure water clusters) has been confirmed by infra-red multiphoton dissociation (IRMPD) measurements of Williams et al [6,7]. The central location of sulfate is also consistent with tandem mass spectrometry-ion trap IR spectroscopy (in the sulfate region) of Neumark et al [8] and photodetachment measurements by Wang et al [9]. The thiocyanate anion (SCN − ) is at the far chaotropic end of the Hofmeister series (beyond perchlorate).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…This led to a greater number of dangling water O-H bonds compared to the sulfate-water case, where the suppression of dangling O-H bonds (compared to pure water clusters) has been confirmed by infra-red multiphoton dissociation (IRMPD) measurements of Williams et al [6,7]. The central location of sulfate is also consistent with tandem mass spectrometry-ion trap IR spectroscopy (in the sulfate region) of Neumark et al [8] and photodetachment measurements by Wang et al [9]. The thiocyanate anion (SCN − ) is at the far chaotropic end of the Hofmeister series (beyond perchlorate).…”
Section: Introductionsupporting
confidence: 70%
“…At the empirical level, lone pentagons or pentagonal prisms (such as those found for pure TIP4P water at n = 5, 10, 15 etc.) and single cubes (as found for TIP4P (H 2 O) 8 ) are not observed for (SCN − )(H 2 O) n due to the low average coordination number that the N atom would adopt. It should be noted that the GM structures for thiocyanate-water clusters with six and eight water molecules (at the EP level) are related to the pure water single cube and pentagonal prism, respectively, but with some water molecules on adjacent edges to the thiocyanate reorienting so as to donate an additional hydrogen bond to the N atom.…”
Section: Comparison Of Thiocyanate-water Clusters With Pure Tip4p Watmentioning
confidence: 98%
“…29,30 Recent studies on mixed bisulfate/nitrate/neutral acid clusters explored the influence of acid solvation on the conjugated base anion and not only showed that the charge localization can vary unexpectedly upon cluster composition, but also revealed the sensitivity of the NO 2 -antisymmetric stretching/NOH-bending mode to the presence of an intact HNO 3 molecule. 31 Studies on bisulfate/ sulfuric acid clusters demonstrated that certain normal modes, mainly those that are localized on the HB network, show a large degree of IRMPD transparency.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed insight into the folding mechanism requires structural information, which is challenging to extract from the photoelectron data. IR photodissociation (IRPD) spectroscopy combined with high-level quantum chemical calculations on microhydrated anions [10][11][12] is able to supply this information and thus leads to a considerably more detailed understanding of this hydration-mediated folding process at the molecular level.Recent IRPD spectra of SA 2À and its monohydrate SA 2À ·H 2 O revealed how the addition of a water molecule affects the spectroscopic signature of the dianion.[13] The water molecule binds to one of the carboxylate groups of the quasi-linear dianion, thus causing characteristic shifts of the intense IR-active carboxylate stretching bands. The two symmetric (n S ) and two antisymmetric (n A ) carboxylate stretching modes in SA 2À are in each case quasi-degenerate, because each pair of modes is weakly coupled as a result of the large distance between the carboxylate groups.…”
mentioning
confidence: 99%